2011
DOI: 10.1007/s00449-011-0633-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of sugarcane molasses “B” as an alternative for ethanol production with wild-type yeast Saccharomyces cerevisiae ITV-01 at high sugar concentrations

Abstract: Molasses "B" is a rich co-product of the sugarcane process. It is obtained from the second step of crystallization and is richer in fermentable sugars (50-65%) than the final molasses, with a lower non-sugar solid content (18-33%); this co-product also contains good vitamin and mineral levels. The use of molasses "B" for ethanol production could be a good option for the sugarcane industry when cane sugar prices diminish in the market. In a complex medium like molasses, osmotolerance is a desirable characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Molasses is a by‐product of the sugar industry, and has been widely used as an economical and convenient carbon source for microbial fermentation due to its high sugar concentration, in the production of lactic acid, ethanol and even some recombinant proteins . In order to explore whether beet molasses being propitious to vitamin B 12 fermentation by P. denitrificans , the nutritional composition of beet molasses was analyzed, and is shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Molasses is a by‐product of the sugar industry, and has been widely used as an economical and convenient carbon source for microbial fermentation due to its high sugar concentration, in the production of lactic acid, ethanol and even some recombinant proteins . In order to explore whether beet molasses being propitious to vitamin B 12 fermentation by P. denitrificans , the nutritional composition of beet molasses was analyzed, and is shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Ethanol has been produced from varieties of substrates ( Table 1 ). First, ethanol production from different wastes such as molasses B [ 41 ], sugar beet pulp [ 42 ], waste from cassava starch production [ 20 ], food waste leachate [ 43 ], and waste newspapers [ 22 ] has been reported. Ethanol production from wastes has two major advantages.…”
Section: Substrate For S Cerevisiaementioning
confidence: 99%
“…In another contradiction, (NH 4 ) 2 SO 4 supplementation to the hydrolysate of cassava pulp (a waste from cassava starch production) did not enhance ethanol production by the yeast [ 20 ]. Another contradiction from [ 41 ] reported that the addition of yeast extract, ammonium sulfate, urea, and their combination to molasses B (sugar rich molasses obtained during the second step of crystallization) did not improve ethanol productivity significantly.…”
Section: Growth Variables Affecting Ethanol Fermentationmentioning
confidence: 99%
“…The substrates recommended for biomass and ethanol production should be efficient and cheap containing a high percentage of carbon source such as molasses B [4] , sugar beet pulp [5] , sugarcane [6] , waste produced during starch production from cassava [7] , food waste [8] , and waste newspapers [9] . These carbon sources are considered as high value products of food source [10] .…”
Section: Introductionmentioning
confidence: 99%